2016
DOI: 10.5194/tc-10-2517-2016
|View full text |Cite
|
Sign up to set email alerts
|

Scaling-up permafrost thermal measurements in western Alaska using an ecotype approach

Abstract: Abstract. Permafrost temperatures are increasing in Alaska due to climate change and in some cases permafrost is thawing and degrading. In areas where degradation has already occurred the effects can be dramatic, resulting in changing ecosystems, carbon release, and damage to infrastructure. However, in many areas we lack baseline data, such as subsurface temperatures, needed to assess future changes and potential risk areas. Besides climate, the physical properties of the vegetation cover and subsurface mater… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 30 publications
2
61
2
Order By: Relevance
“…Only general classes can be derived, and applicability has been proven in permafrost transition zones only. The relevant types are peatlands (with differentiation by vegetation cover) [73] and ecotypes that distinguish between low and tall shrubs, as well as their characteristic moss and organic layers [75]. This demand for details on shrubs coincides with statements in studies for numerical permafrost modeling [1,80].…”
Section: Challenges and Promising Approachesmentioning
confidence: 64%
See 1 more Smart Citation
“…Only general classes can be derived, and applicability has been proven in permafrost transition zones only. The relevant types are peatlands (with differentiation by vegetation cover) [73] and ecotypes that distinguish between low and tall shrubs, as well as their characteristic moss and organic layers [75]. This demand for details on shrubs coincides with statements in studies for numerical permafrost modeling [1,80].…”
Section: Challenges and Promising Approachesmentioning
confidence: 64%
“…A land cover map was produced, and values for peat thickness and vegetation height were associated with the resulting classes. Ground temperatures have been up-scaled using an ecotype land cover map (from among other sources, Landsat, stratified NDVI and unsupervised classification of Jorgenson et al [74]) on a regional scale [75]. The available classes were grouped into four clusters representing certain ground temperature ranges in a permafrost transition zone in Alaska.…”
Section: Permafrost Subsurface and Land Surface Featuresmentioning
confidence: 99%
“…The effect of ground warming as a result of tundra shrubification has been discussed in previous studies (Lynch et al 1999, Chapin et al 2000, Cable et al 2016. However, the ramification of snow-shrub interactions is not linear and depends on multiple factors (Sturm et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Shifting climate conditions in the Arctic are driving evolution of permafrost landscapes that include changes in, and complex interactions between, plant productivity and species distribution, permafrost degradation, hydrologic processes, and the terrestrial carbon cycle and energy balance (AMAP 2017). Increasing migration of shrubs into tundra could lead to positive changes in surface energy balance and net loss of carbon from the ecosystem (Bret-Harte et al 2002, Cable et al 2016. Shrub-snow interaction could boost winter heating by up to 70% for exposed shrubs, leading to warmer soil temperature below shrubs over winter periods (Sturm et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…) or using an ecotype approach (Cable et al . ). Upscaling of soil organic carbon in mountainous NE Greenland based on a vegetation map identified that vegetation is a poor indicator for the burial history of organic matter in areas with sedimentation (Palmtag et al .…”
mentioning
confidence: 97%